PENGARUH MODEL PEMBELAJARAN COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) DALAM MENINGKATKAN KEMAMPUAN LITERASI MEMBACA PADA SISWA KELAS III SD NEGERI 060921 MEDAN SUNGGAL - Selviana Debora Sianipar; Reflina Sinaga; Anton Sitepu; Rumiris Lumban Gaol; Dyan Wulan Sari HS; Patri Janson Silaban (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to determine the influence of the Cooperative Integrated Reading And Composition learning model in improving the reading literacy ability of grade III students of SD Negeri 060921 Medan Sunggal. This study uses a quantitative research method. The population of this study is grade III in SD Negeri 060921 with a total of 30 students. Sampling used purposive sampling of 30 students. To find out the students' initial ability, the researcher conducted a pretest with an average score of 43.53 in the bad category. After the researcher used the Cooperative Integrated Reading And Composition learning model, it was shown that students' reading literacy skills experienced an increase with an average score of 83.73 in the good category. This study can be proven from the results of the calculation of the correlation coefficient of 0.941, meaning (0,941) ≥ (0.361) then Ha is accepted. Therefore, there is a strong influence between the Cooperative Integrated Reading And Composition learning model in improving the reading literacy ability of third grade students of SD Negeri 060921 Medan Sunggal. It can be seen from the results of the t-test test which is 14.7139≥ 1.697 so that it states that Ha is accepted. This shows that there is a significant positive influence of the use of the Cooperative Integrated Reading And Composition learning model in improving the reading literacy skills of grade III students of SD Negeri 060921 Medan Sunggal for the 2024/2025 academic year.